SISTEM PENGEMBANGAN AGRIBISNIS HORTIKULTURA BERKELANJUTAN DAN BERDAYA SAING TINGGI DI KAWASAN TIMUR INDONESIA - MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2001)
To develop the Indonesia East Region (KTI) in second long-term development (PJPII) is a necessary and can not delayed again after marginalized in first long-term development(PJP I). Yet, development of Indonesia east region must be based on comparative andcompetitive advantage and orientation on national and regional importance (province, district)region mentioned.Agribusiness of horticulture with growth engine of ‘on-farm agribusiness’ is mainalternative developed in Indonesia east region, cause supported by natural resources, humanresources, social capital and the other natural comparative. Then, agribusiness hoped to begrowth motor for regional and national economy.To develop the horticulture agribusiness in Indonesia east region (KTI) should be useconcept of sustainability horticulture agribusiness development. Its mean, use the naturalresources (land, forestry, water) and man made resources (fertilizer, technology, etc) withlower intensity, so there are preservation of natural resources, even increase its quality toheritage for next young generation.To reach the high competitiveness of agribusiness products in Indonesia east regionare to step aside of substance and organization constraints, to overcome the problems facedby agribusiness man, to make small the weakness, and to increase role of government andother involve institution to facilitate development of agribusiness in Indonesia east region.To obtain the success of agribusiness development in Indonesia east region, let studyfrom the success story of Thailand agribusiness development (good can be imitated). Thesuccess export of Thailand agribusiness products is result of handwork for many years whoinvolve many agents and stakeholders, from king or princess until agribusiness workers, fromlecturer or researchers until general community, and from government or finance institutiontill entrepreneurships. All of this effort continuously always markets oriented. Mostimportant is activity of agents directly support of agribusiness export, like Thailand AirwaysCargo.